Reflections on Leadership - Campbell, Carol A. (American Health Information Management Association, 2013)
Webster's dictionary offers numerous synonyms and related words for the word lead; the list includes words such as chief, commanding, first, foremost, high, preeminent, controlling, directing, reigning, sovereign, and superior. Some individuals (perhaps too many) in positions of authority rely very heavily on characteristics associated with these terms. Abusive leaders exploit their power and “lead” through intimidation and their ability to withhold rewards and distribute punishment. This article explores why some people are bad bosses and suggests six obligations of leaders who aspire to fulfilling the role of leadership done right.